One hundred physics visualizations using MATLAB - Green, Dan, 1943-; World Scientific (Firm) ([Hackensack,] New Jersey : World Scientific, 2014)
"This book provides visualizations of many topics in general physics. The aim is to have an interactive MATLAB script wherein the user can vary parameters in a specific problem and then immediately see the outcome by way of dynamic "movies" of the response of the system in question. MATLAB tools are used throughout and the software scripts accompany the text in symbolic mathematics, classical mechanics, electromagnetism, waves and optics, gases and fluid flow, quantum mechanics, special and general relativity, and astrophysics and cosmology. The emphasis is on building up an intuition by running many different parametric choices chosen actively by the user and watching the subsequent behavior of the system. Physics books using MATLAB do not have the range - or the intent - of this text. They are rather steeped in technical detail. Symbolic math is used extensively and is integral to the aim of using MATLAB tools to accomplish the technical aspects of problem solving"--
Includes bibliographical references (pages 289-290) and index.
Keywords: MATLAB; Physics -- Data processing; Numerical analysis -- Computer programs